Impact of expansion level on flow field of a circular duct at high Mach numbers. (2021) - Khan, Sher Afghan; Chaudhary, Zakir Ilahi; Baig, Maughal Ahmed Ali; Ridwan,; Delvi, Hamza Afser; Faheem, Mohammed
Abstract: The study discusses the impact of different nozzle pressure ratios and the duct sizes on the duct's flow field. The duct diameter was 16 mm, and the inertia levels at which the experiments were done are M = 1.87, 2.2, and 2.58. Dynamic regulators as an orifice stationed in the wake region at 6.5 mm from the central jet axis. At M = 1.87, when the jets are operated at NPR = 3, the duct size 1D and 2D, the wall pressure assumes high, and control is not helpful. There is no impact on the flow control management at Mach 2.2 for duct length 1D and 2D at NPR = 3, 5, and 7. But for this Mach, this trend is limited at NPR = 3 and 5. When the Mach value is 2.58, the wall pressure assumes ambient condition, and control has minimal impact on the duct's flow pattern. When the duct length is 10D, the stream field turns oscillatory for Mach investigated. The control device does not impact the inside flow negatively.